Evaluating the readiness of special education doctoral students to apply the standards of evidence‐based practice to single‐case research. Issue 1 (9th March 2015) - Mayton, Michael R.; Zhang, Jie; Carter, Stacy L.; Suppo, Jennifer L.
Abstract : How well doctoral students in special education are prepared to evaluate research as evidence‐based practice (EBP) is likely to impact their careers, as well as the teachers they will train. In developing a method for evaluating the readiness of small cohort groups of doctoral students to apply a research‐based model of EBP, an instrument and procedure were refined in a pilot evaluation and implemented within a multiple baseline design across participants. Participants' independent and instrument‐guided performance in rating published research was compared to the ratings of two experts in single‐case research design, yielding proportions of agreement across evaluation conditions. Results indicated group readiness to independently conduct the EBP evaluation and individual differences in readiness indicating the need for remediation.